A Study of a DC/AC Conversion Structure for Photovoltaic System Connected to the Grid with Active and Reactive Power Control. (7th July 2021) - Brahmi, Houda; Dhifaoui, Rachid
Abstract : DC/AC conversion of photovoltaic energy is in great demand for AC applications; the supply of electrical machines and transfer energy to the distribution network is a typical case. This work is realized in this context and presents a new structure for the transfer of photovoltaic energy to the electricity grid. This structure is based on a push-pull converter connected to a three-phase DC/AC inverter. In particular, a great interest is focused on the steady operating conditions of energy transfer. The study also develops the limits and the feasibility of the PV energy transfer to the grid of the proposed structure. Injecting photovoltaic energy into the grid with maximum active power and zero reactive power is also considered for the dynamic regime. Support simulations are carried out to validate the proposed control strategy.